Construct Validity of Indonesian Vocational Interest Test (Tes Minat Vokasional Indonesia) to Measure Interest of Vocational School Student - Ayuni, Rifqa Putri; Hakim, Moh. Abdul (Psympathic : Jurnal Ilmiah Psikologi, 2025)
This study aims to comprehensively evaluate the construct validity of Tes Minat Vokasional Indonesia (TMVI) in gauging the interests of vocational high school students. To achieve the stated objective, confirmatory factor analysis (CFA) was adopted as the study approach. Accordingly, the respondents of this investigation comprised 474 students from SMKN 2 Surakarta. The obtained results showed that model fit indicators such as CFI, TLI, SRMR, and RMSEA, all fell within the designated ranges (CFI and TLI ≥ .90, SRMR ≤ .08, and RMSEA ≤ .06). This suggest that TMVI had a rather good construct to measure the interests of vocational high school students. However, the factor loading analysis conducted reflected that some items showed factor loading values below the designated threshold (≥0.15). This observation invariably imply that the contribution of the items having low factor loading values to the measured construct was minimal. A plausible reason for this is because the vocabulary used by vocational high school pupils was not age-appropriate. Therefore, if TMVI is to be used to gauge the interests of vocational high school students, its wordings must be modified.